The perception, behaviours and acceptance of Covid-19 vaccine among Malay senior citizens: A qualitative study - Sualman, Ismail; Ayub, Suffian Hadi (UUM Press, 2022)
Despite concerted efforts taken since the launched of immunization campaign for Malaysians, the country still wary of individuals who consistently disputing the validity and legality of the vaccine. Further to that, there are also Malaysia citizens who do not believe in the effectiveness of the vaccine which lead to refusal in receiving it voluntarily. The study aimed to (i) to explore the understanding of the Malay senior citizens on health communication campaigns related to the COVID-19 vaccination programmes, (ii) to review the sources of information used by the senior citizens in obtaining information related to the vaccine and COVID-19, and (iii) to explore the behaviours of the senior citizens and their acceptance of the COVID-19 vaccine. The study involved 10 Malay senior citizens within the range age group of 55-65 years. In order to seek diverse insights on the information seeking behaviour and the preferred sources, the study focused on the influence of cultural, religious diversity and the implementation of health communication campaigns by the government on the effectiveness of the COVID-19 vaccine. Further, the study also explored the level of understanding and perception on the effectiveness of COVID-19 vaccine among senior citizens. Qualitative methodology was applied using focus group discussion in the data collection, and NVIVO software was used for analysis. The study found hesitancy on the vaccine resulting from the unsure sources of information. Senior citizens from Malay community were very concerned on receiving the vaccine. Additionally, the result indicated that the national immunisation campaign is less effective especially to those who reside in rural areas. The majority of the participants obtained information sources related to vaccines and COVID-19 through social media compared to mainstream media. Inasmuch the overseas media provided more authentic information than the local media, it was equally significant that the informants also found the information by the National Security Council (MKN) and the Ministry of Health Malaysia (MOH) to be authentic and were always referred to.